Use of rapid test for the diagnosis of human immunodeficiency virus (HIV) infection in parturients - Capobiango, Jaqueline Dario; Baldy, José Luís da Silveira; Reiche, Edna Maria Vissoci; Morimoto, Helena Kaminami; Costa, Tatiana Inácio; Silva, Cristina Mara da; Matsuo, Tiemi (Revista de Ciências Médicas e Biológicas, 2010)
The diagnosis of human immunodeficiency virus (HIV) in parturient women is used to prevent or change the course of HIV perinatal transmission through the zidovudine prophylaxis regimen. The aims of this study were to determine the prevalence of the HIV infection using the rapid test, to evaluate its acceptance for the diagnosis of HIV infection, and to determine the risk factors for HIV infection in parturients. Interview and a rapid test for anti-HIV were carried out on 4,341 parturients attended at two main public maternities (Maternity of the University Hospital and Municipal Maternity “Lucilla Ballalai”), in the city of Londrina, Paraná, Brazil, from May, 2000, to September, 2001. The rapid test was positive in 23 (0.52%) parturients evaluated. Of them, the seropositivity in the conventional (screening and confirmatory) tests was obtained in 19 (0.44%; 95% CI: 0.27 – 0.70). The rate of the rapid test acceptance was 99.7%. Among HIV-infected. parturient it was found higher frequency (52.6%) of intravenous drug-user sexual partner (Odds ratio 51.63, 95% CI: 18.67-143.51, p< 0.0001) when compared with HIV-uninfected parturients, and also with a diagnosed seropositive partner (42.1%) when compared with HIV-uninfected parturients (Odds ratio 1011.88, 95% CI: 201.87-5766.26, p<0.0001). However, 15.8% of the HIV-infected parturient denied the existence of any risk factor for HIV infection. The results of this study emphasize the useful of the rapid test to diagnose the HIV infection in all parturient.